2022
DOI: 10.4168/aair.2022.14.1.73
|View full text |Cite
|
Sign up to set email alerts
|

Natural History and Influencing Factors of Chronic Urticaria in Children

Abstract: Purpose Chronic urticaria (CU) can reduce the quality of life of children and their parents, but there are only a few studies on the course of CU in children. This study aimed to investigate the natural course of CU in children and identify the factors that influence its prognosis. Methods We evaluated 77 children diagnosed with CU, who were monitored for at least 48 months. Subjects were classified as either chronic spontaneous urticaria (CSU) or other CU, and the clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…2 In children, prevalence is estimated to be 0.1-0.3%. 3 Even though it has been classically known that children have a lower prevalence, 4 there are reports of a higher prevalence in pediatric patients (1.43%) compared with adults (0.86%). 2 Regarding the natural history of CU, there seems to be a wide variation in remission rates.…”
Section: Introductionmentioning
confidence: 99%
“…2 In children, prevalence is estimated to be 0.1-0.3%. 3 Even though it has been classically known that children have a lower prevalence, 4 there are reports of a higher prevalence in pediatric patients (1.43%) compared with adults (0.86%). 2 Regarding the natural history of CU, there seems to be a wide variation in remission rates.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported that 5.5% of pediatric patients with CSU had G. duodenalis, D. fragilis, and Blastocystissp. (Kim et al, 2022). Another study reported a 10% prevalence of IPI in CSU pediatric patients, and the most prevalent parasites were E. vermicularis, D. fragilis, G. duodenalis, and Blastocystis sp.…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, total levels of IgE were positively associated with disease duration. (r = 0.262, p = 0.021) ( 77 ). In CU adults, high IgE levels correlated with disease severity and duration, but not the clinical course of the disease ( 64 , 78 ).…”
Section: Cu and Atopic Diseasesmentioning
confidence: 99%